De-Escalation of Antiplatelet Therapy in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Clinical Trials. (March 2019) - Kheiri, Babikir; Osman, Mohammed; Abdalla, Ahmed; Chahine, Adam; Ahmed, Sahar; Osman, Khansa; Bachuwa, Ghassan; Hassan, Mustafa; Bhatt, Deepak L.
Aims: Patients with acute coronary syndrome undergoing percutaneous coronary intervention (PCI) are recommended to be placed on potent P2Y12 blockade. However, the long-term bleeding risk is high. Therefore, despite no definitive evidence, switching to clopidogrel beyond the acute phase is common. We aimed to evaluate the clinical outcomes of antiplatelet de-escalation compared with continuation in patients treated with PCI. Methods: We searched databases for randomized clinical trials (RCTs) that evaluated the safety and efficacy of antiplatelet de-escalation compared with continuation in patients treated with PCI. Pooled summary estimates were calculated. Results: We included 3 RCTs with 3391 patients (median follow-up: 12 months). Compared with the continued group, the net clinical outcome (composite of bleeding or thrombotic events) was significantly reduced in the group switched to clopidogrel (8.7% vs 12.1%; risk ratio [RR]: 0.64; 95% confidence interval [CI]: 0.43-0.97; P = .03). However, there were similar clinical outcomes between groups for major adverse cardiovascular events (MACE; RR: 0.78; 95% CI: 0.55-1.11; P = .17), all Bleeding Academic Research Consortium (BARC) types bleeding (RR: 0.61; 95% CI: 0.33-1.11; P = .10), or BARC types ≥2 bleeding (RR: 0.49; 95% CI: 0.19-1.26; P = .14). Conclusions: Our results suggest a net clinical benefit of de-escalation therapy shortly after PCI, without increased risk of MACE. Larger randomized trials will be necessary to confirm these findings.